Pulpit in Parliament ; Puritanism during the English civil wars, 1640-1648 - Wilson, John Frederick (Princeton University Press, 1969)
Before the outbreak of hostilities between Charles I and the Long Parliament, the King had authorized a regular monthly fast for the realm which members of parliament later adopted as a program of national humiliation. At the invitation of individual members of parliament, two preachers, generally leading puritan clerics connected with the Westminster Assembly, which had been convened for the purpose of reforming the Church of England, were invited to speak. Drawing from some 240 published sermons, Professor Wilson presents a survey of the program, giving detailed scrutiny to the form and contents of the sermons. His aim throughout is to clarify the puritans' conceptions of the relationship between their religious movement and the political events of the period, and to assess the importance of these sermons for the interpretation of Puritanism. Originally published in 1969. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Keywords: Puritans -- England.; Preaching -- England -- History.; Prédication -- Angleterre -- Histoire.; RELIGION -- Christian Ministry -- Preaching.; Preaching; Puritans; England; Puritanismus; Englischer Bürgerkrieg; England -- Bürgerkrieg.; History